A flexible pressure sensor based on PEDOT coated polyester nonwoven fabric for low-pressure range. (1st March 2022) - Zhang, Jia-wen; Zhang, Yan; Li, Yuan-yuan; Ye, Xu; Wang, Ping; Xu, Yu-kang
Abstract: Three most common methods for preparing PEDOT (poly(3, 4-ethylenedioxythiophene)) are studied, including vapor phase polymerization (VPP), in-situ dipping (ISD) and solution deposition (SD) techniques. The PEDOT coated nonwoven fabric (PEDOT@NWF) composites were successfully fabricated via these three processes and have been proven to be conductive and equipped with piezoresistive properties. For each preparation method, factors that may affect product properties, such as concentrations of reagents, reaction temperature, reaction time, etc were explored to summarize the optimal parameters. The PEDOT@NWF composites prepared via different fabrication techniques were analyzed and compared through a series of tests and characterizations. The sensing performance of as-prepared pressure sensors are also been studied. The experimental results demonstrate that PEDOT@NWF prepared by VPP method (PEDOT@NWF-VPP) has the fastest response time (80 ms) and recovery time (40 ms), the composite prepared by ISD method (PEDOT@NWF-ISD) has the highest sensitivity for the pressure range less than 5 kPa (21.162 kPa −1 ) and long-term cycle stability (over 5000 cycles). Sensor utilized PEDOT@NWF-ISD as the piezoresistive layer was assembled and used to detect small pressure such as voice vibrations and air flow, implying that this designed pressure sensor has promising potential in the application of wearable electronic devices and healthcare monitors.